2005
DOI: 10.1159/000086979
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of First-Line Sequential Chemotherapy with Gemcitabine-Carboplatin Followed by Docetaxel in Patients with Advanced Non-Small Cell Lung Cancer

Abstract: Rationale: Despite the use of novel chemotherapeutic agents, patients with advanced non-small cell lung cancer (NSCLC) continue to show a poor survival. Objectives: To assess the safety and efficacy of a novel sequential and putatively non-cross-resistant chemotherapy regimen. Methods: Eligibility included: stages IV and IIIB (malignant pleural effusion), performance status 0–1, and adequate renal, hepatic and bone marrow function. Patients with previously treated and controlled brain metastases were not exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
2
12
0
1
Order By: Relevance
“…Patients achieved an RR of 44% and the 1-year OS and PFS rates were 59% (median, 13.3 months) and 14% (median, 6.6 months), respectively. The results from this study compared favorably with those of another phase II study of uncustomized treatment in similar patient populations (RR, 24%; median OS, 6.7 months) (Chiappori et al, 2005). Collectively, these data suggest that the identification of patients with low expressions of ERCC1 and RRM1 allows for a strategy of individualized chemotherapy in this population, which may result in an improved outcome (Huang et al, 2006;Simon et al, 2007).…”
Section: Biomarkers For Chemotherapysupporting
confidence: 56%
“…Patients achieved an RR of 44% and the 1-year OS and PFS rates were 59% (median, 13.3 months) and 14% (median, 6.6 months), respectively. The results from this study compared favorably with those of another phase II study of uncustomized treatment in similar patient populations (RR, 24%; median OS, 6.7 months) (Chiappori et al, 2005). Collectively, these data suggest that the identification of patients with low expressions of ERCC1 and RRM1 allows for a strategy of individualized chemotherapy in this population, which may result in an improved outcome (Huang et al, 2006;Simon et al, 2007).…”
Section: Biomarkers For Chemotherapysupporting
confidence: 56%
“…This was found to be the case, with data indicating an unprecedented 12-month survival rate of 62%. Comparison with another study (MCC-12621) conducted at the same institution by the same physicians and with matching referral patterns, staging and enrolment criteria revealed that results obtained in the MADeIT study were close to 50% better (Table 1) [40]. Similarly, results from another study (E1594) revealed that the tailored treatment used in the MADeIT trial produced 12-month survival values that were almost double those previously observed [22].…”
Section: Rrm1-and Ercc1-based Chemotherapy Selectionmentioning
confidence: 60%
“…When sequential chemotherapy offered, it is possible to overcome the drug resistance of single regimen used for a relatively longer period. Actually, the debate about maintenance therapy for advanced NSCLC had been re-ignited in recent years (Hosoe et al, 2003;Grossi et al, 2004;Chiappori et al, 2005;Pallis et al, 2006). The results of several randomized phase III studies reported showing a significant advantage of maintenance treatment in advanced NSCLC (Ciuleanu et al, 2007;Fidias et al, 2009;Cappuzzo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%